Tolerância - Santos, Murilo Alves dos [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The screenplay for the short film Tolerance is a project whose goal is to generate discussion about intolerance, which falls on the minority cultures in contemporary society. Even preserving their Brazilianness, through the art direction, it can cross borders as it does not have dialogues, and addresses current realities that underlie different cultures, even the most liberal and democratic. This project can achieve the interests of various groups, making it an excellent tool for generating discussion and debate in all social and educational levels

O roteiro do curta-metragem “Tolerância” é um projeto cujo objetivo é gerar discussão a respeito da intolerância que recai sobre as culturas das minorias na sociedade contemporânea. Mesmo preservando sua brasilidade, por meio da direção de arte, ele poderá atravessar fronteiras, visto que não possui diálogos e aborda realidades atuais que perpassam diversas culturas, mesmo as mais liberais e democráticas. Este projeto consegue atingir o interesse de diversos públicos, tornando-o uma excelente ferramenta geradora de discussão e debate, em todos os níveis sociais e educacionais
Keywords: Tolerancia; Cultura; Pluralismo cultural; Identidade; Toleration; Culture; Cultural pluralism